2005
DOI: 10.1016/j.micres.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Phg, a novel member of the autotransporter family present in Bordetella species

Abstract: Several proteins encoded in the genomes of Bordetella species show significant sequence similarity to the autotransporter domains of surface exposed or secreted virulence factors of bordetellae such as pertactin, tracheal colonization factor or Vag8. One of these putative autotransporters, provisionally termed Phg, is encoded by the pertactin homologous gene (phg), which is highly conserved in Bordetella pertussis, B. bronchiseptica and B. parapertussis, but absent in B. avium and B. petrii. In contrast to hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous work has shown that the cleavage of the passenger domains of several members of the pertactin (Prn) family of autotransporters produced by B. pertussis occurs after an asparagine residue (Middendorf et al , 2005). While the β domains of these proteins are closely related to each other, they are only weakly related to the β domains of the SPATEs (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that the cleavage of the passenger domains of several members of the pertactin (Prn) family of autotransporters produced by B. pertussis occurs after an asparagine residue (Middendorf et al , 2005). While the β domains of these proteins are closely related to each other, they are only weakly related to the β domains of the SPATEs (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminus of Vag8 has high sequence identity to other B . pertussis autotransporter proteins including Prn [ 40 ]. Previous data indicated that unlike most autotransporters [ 41 , 42 ], the passenger domain of Vag8 would not be cleaved [ 5 ].…”
Section: Discussionmentioning
confidence: 99%